Anode active material, secondary battery, and electronic device

A composite particle structure with irregular and ordered carbon regions enhances active ion diffusion, addressing capacity and stability issues in secondary battery electrodes, thereby improving energy density and charging performance.

JP7611303B2Active Publication Date: 2025-01-09NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023098951
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-06-16
Publication Date
2025-01-09
Estimated Expiration
2043-06-16

Smart Images

  • Figure 0007611303000008
    Figure 0007611303000008
  • Figure 0007611303000009
    Figure 0007611303000009
  • Figure 0007611303000010
    Figure 0007611303000010
Patent Text Reader

Abstract

To provide a negative electrode active material that can improve the gram capacity of the negative electrode active material and the active ion diffusion coefficient inside it, further improve the energy density of the secondary battery, and improve the cycle performance, rate performance, and rapid charging ability of the secondary battery, and a secondary battery including the negative electrode active material.SOLUTION: In a negative electrode active material, a secondary battery, and an electronic device, the negative electrode active material includes multiple composite particles, the composite particle includes a first region and a second region, and the first region has a disordered carbon structure and the second region has an ordered carbon structure and / or a metal oxide structure.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of energy storage. In particular, the present invention relates to negative electrode active materials, secondary batteries, and electronic devices. [Background technology]

[0002] Secondary batteries have the advantages of high operating voltage, wide applicable temperature range, low self-discharge rate, etc., and are widely used in the fields of mobile electronic devices, home appliances, electric vehicles, etc. With the continuous development of products using them, each field has higher requirements for the capacity, energy density, charge and discharge rate, and cycle stability of secondary batteries. At present, the negative electrode material of commercialized secondary batteries is still mainly graphite material, and the graphite negative electrode has advantages such as high electrical conductivity and high stability, but its theoretical specific capacity is low, and the specific capacity of the current graphite negative electrode is already close to its theoretical maximum value of 372mAh / g, and the expansion of the graphite negative electrode is serious in the fast charging system, which causes the deterioration of the life and reliability of the secondary battery.

[0003] Hard carbon materials have a high reversible specific capacity compared to graphite materials, generally 500mAh / g to 700mAh / g, and can reach 1000mAh / g or more, and have excellent rate charge / discharge performance. However, because the potential of the electrode where the hard carbon material is located is too high, there are disadvantages such as potential hysteresis (i.e., the lithium absorption potential is smaller than the lithium release potential) and large irreversible capacity in the first cycle, which affects the commercialization process of applying hard carbon materials to negative electrodes. Therefore, in order to expand the application field of hard carbon materials, it is necessary to further study hard carbon materials with excellent electrochemical performance. Summary of the Invention

[0004] In view of the above problems existing in the prior art, the present invention provides a negative electrode active material and a secondary battery including the negative electrode active material, which can improve the gram capacity of the negative electrode active material and the active ion diffusion coefficient therein, and further improve the energy density of the secondary battery, and can improve the cycle performance, rate performance, and rapid charging capability of the secondary battery.

[0005] The first aspect of the present invention provides an anode active material comprising a composite particle, the composite particle comprising a first region and a second region, the first region having an irregular carbon structure, the second region having an ordered carbon structure and / or a metal oxide structure, and the surface of the composite particle comprising the first region. According to the research of the inventor of the present invention, it was found that the first region having an irregular carbon structure, such as a hard carbon material region, is itself irregular amorphous graphite, has an irregular internal structure arrangement, and at the same time has many pore structures, so that its true density and compressed density are not high. By introducing the first region having an irregular carbon structure and the second region having an ordered structure into the composite particle, the present invention can not only maintain the capacity level of the anode active material, but also effectively improve the compressed density of the anode active material, thereby improving the energy density of the secondary battery. In addition, the second region having an ordered structure can effectively reduce the free path of active ions, improve the internal diffusion kinetics of the negative electrode active material, reduce the internal polarization of the negative electrode active material, and improve the fast charging performance, rate performance, and cycle performance of the secondary battery.

[0006] According to some embodiments of the present invention, the first region includes a first active material, the first active material includes hard carbon and / or soft carbon, which has a larger d002 spacing and micropore content after being heat-treated at 1000° C. or higher than the soft carbon, and can provide more active ion release sites.

[0007] According to some embodiments of the present invention, the second region comprises a second active material, the second active material comprising at least one of graphite, graphene, carbon nanotubes, lithium oxide, and a transition metal oxide.

[0008] According to some embodiments of the present invention, the average particle size of the graphite is 10 nm to 1000 nm, the average sheet diameter of the graphene is 10 nm to 2000 nm, the average diameter of the carbon nanotubes is 10 nm to 2000 nm, the average particle size of the lithium oxide is 10 nm to 1000 nm, and the average particle size of the transition metal oxide is 10 nm to 1000 nm, and preferably, the average particle size of the graphite is 20 nm to 300 nm, the average sheet diameter of the graphene is 20 nm to 500 nm, the average diameter of the carbon nanotubes is 20 nm to 500 nm, the average particle size of the lithium oxide is 20 nm to 300 nm, and the average particle size of the transition metal oxide is 20 nm to 300 nm. The active ions are more easily diffused in the second active material, and in order to improve the diffusion ability of the active ions in the negative electrode, it is necessary to increase the contact area between the first region and the second region. When the average particle size, average sheet size, or average diameter of the second active material is within this range, the contact area between the first region and the second region is increased, the diffusion ability of active ions is improved, and the rate performance, rapid charging performance, and cycle performance of the secondary battery are further improved.

[0009] According to some embodiments of the present invention, the second region is randomly or layeredly distributed in the composite particle, which can effectively reduce the free path of active ions, increase the solid-state transmission rate of active ions, and further improve the rate performance, fast charging performance and cycle performance of the secondary battery.

[0010] According to some embodiments of the present invention, the composite particles are primary particles. In some embodiments, the particle size of the composite particles satisfies 3 μm≦Dv50≦12 μm. When the particle size of the composite particles is in the above range, the dynamic performance of the secondary battery can be further improved, and the rate performance, fast charging performance and cycle performance of the secondary battery can be improved.

[0011] According to some embodiments of the present invention, the X-ray photoelectron spectroscopy spectrum of the negative electrode active material has a characteristic peak in the range of 283 eV to 288 eV that corresponds to the disordered carbon structure in the first region in the composite particle.

[0012] According to some embodiments of the present invention, the negative electrode active material has an ID / IG ratio of 0.6 to 1.3, and ID is a Raman shift of 1300 cm -1 ~1400cm -1 IG represents the peak intensity in the range where the Raman shift is 1550 cm -1 ~1650cm -1 The peak intensity in the range is expressed as:

[0013] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in the 2θ range of 18° to 30° corresponding to the disordered carbon structure in the first region of the composite particle, and in some embodiments, the half-width of the characteristic peak is 4° to 12°.

[0014] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in the 2θ range of 26° to 27° that corresponds to graphite or carbon nanotubes (CNTs) in the second region.

[0015] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak corresponding to lithium titanate in the second region in at least one of 2θ ranges of 18° to 19°, 35° to 36°, and 43° to 44°.

[0016] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak corresponding to triiron tetroxide in the second region in at least one of 2θ ranges of 30° to 31°, 35° to 36°, 42.5° to 43.5°, 56.5° to 57.5°, and 62° to 63°.

[0017] According to some embodiments of the present invention, the specific surface area of ​​the negative electrode active material is less than 1 m 2 / g~50m 2 When the specific surface area of ​​the negative electrode active material is within the above range, the rate performance, rapid charge performance, and cycle performance of the secondary battery can be further improved.

[0018] A second aspect of the present invention provides a secondary battery including a negative electrode, the negative electrode including a negative electrode active material layer and a current collector, the negative electrode active material layer including the negative electrode active material of the first aspect.

[0019] According to some embodiments of the present invention, the porosity of the negative electrode active material layer is 10% to 50%. When the porosity of the negative electrode active material layer is within the above range, the rate performance, rapid charging performance and cycle performance of the secondary battery can be further improved. If the porosity is too large, the contact points between the negative electrode active material particles are reduced, and the internal resistance of the secondary battery is increased. If the porosity is too small, the wettability of the electrolyte is poor, the transport path of the active ions is lengthened, and the shuttle of the active ions between the positive and negative electrodes is hindered, and the negative electrode pieces that are not in contact with the electrolyte cannot participate in the electrochemical reaction inside the secondary battery, and at the same time, the interface resistance of the secondary battery is increased, which affects the rate performance, discharge capacity and service life of the secondary battery.

[0020] According to some embodiments of the present invention, the adhesive strength between the negative electrode active material layer and the current collector is 3N / m to 30N / m. When the adhesive strength between the negative electrode active material layer and the current collector is in this range, the rate performance, rapid charging performance and cycle performance of the secondary battery can be further improved. If the adhesive strength between the negative electrode active material layer and the current collector is too low, peeling and burrs are likely to occur in the roll press and slit process, which causes safety problems for the secondary battery. If the adhesive strength between the negative electrode active material layer and the current collector is too high, the adhesive strength between the active material and the current collector is too large, the proportion of the binder is high, the internal resistance of the secondary battery is likely to be high, the dynamic loss is serious, and the attenuation of the long cycle performance is accelerated.

[0021] A third aspect of the present invention provides an electronic device including the secondary battery of the second aspect.

[0022] The present invention provides a composite particle having a first region with an irregular carbon structure and a second region with an ordered carbon structure and / or a metal oxide structure, thereby improving the compression density of the negative electrode active material layer and the energy density of the secondary battery while maintaining the capacity level of the negative electrode active material. The second region with an ordered structure further improves the internal diffusion kinetics of the negative electrode active material, so that the secondary battery has a high active ion diffusion coefficient in the later charging and discharging period, and can improve the rapid charging ability, rate performance and cycle performance of the secondary battery. In addition, the preparation method of the present invention is simple, easy to operate and control, and suitable for industrialized production. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a TEM image of the negative electrode active material according to Example 4 of the present invention. [Diagram 2] FIG. 2 is an SEM image of the negative electrode active material according to Example 4 of the present invention. [Diagram 3] FIG. 3 is a carbon micro spectrum of the X-ray photoelectron spectroscopy spectrum of the negative electrode active material of Example 4 of the present invention. [Figure 4] FIG. 4 is a Raman spectrum of the negative electrode active material according to Example 4 of the present invention. [Diagram 5] FIG. 5 is an XRD spectrum of the negative electrode active material according to Example 4 of the present invention. [Figure 6] FIG. 6 is a schematic diagram showing the internal arrangement of negative electrode active materials in some embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] For the sake of brevity, only some numerical ranges are specifically disclosed in the present invention. However, any lower limit may be combined with any upper limit to form a range not expressly described, and any lower limit may be combined with another lower limit to form a range not expressly described, and likewise, any upper limit may be combined with any other upper limit to form a range not expressly described. Furthermore, each point or individual value disclosed individually may be combined with any other point or individual value, either as a lower limit or upper limit, or with another lower limit or upper limit to form a range not expressly described.

[0025] In the description of the present invention, unless otherwise specified, the terms "greater than or equal to" and "less than or equal to" include extreme values.

[0026] Unless otherwise specified, the terms used in the present invention have the general meanings commonly understood by those skilled in the art. Unless otherwise specified, the values ​​of each parameter referred to in the present invention can be measured using various measurement methods commonly used in the art (for example, can be measured according to the method described in the examples of the present invention).

[0027] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms, refers to any combination of the listed items. For example, if items A and B are listed, the short phrase "at least one of A and B" refers to A only, B only, or A and B. In another example, if items A, B, and C are listed, the short phrase "at least one of A, B, and C" refers to A only, B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or all of A, B, and C. Item A may include a single component or multiple components. Item B may include a single component or multiple components. Item C may include a single component or multiple components.

[0028] The present invention will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are used to illustrate the present invention and do not limit the scope of the present invention.

[0029] 1. Negative electrode active material The negative electrode active material provided by the present invention comprises a composite particle, the composite particle comprises a first region and a second region, the first region has an irregular carbon structure, the second region has an ordered carbon structure and / or a metal oxide structure, and the surface of the composite particle comprises the first region. According to the research of the inventor of the present invention, it was found that the first region having an irregular carbon structure, such as a hard carbon material region, is itself irregular amorphous graphite, the arrangement of the internal structure is irregular, and at the same time, many pore structures exist, so that the true density and compressed density of the first region are not high. The present invention can maintain the capacity level of the negative electrode active material by introducing the first region having an irregular carbon structure and the second region having an ordered structure into the composite particle, and the densely arranged second region can effectively increase the compressed density of the negative electrode active material, thereby increasing the energy density of the secondary battery. In addition, the second region having an ordered structure can effectively reduce the free path of active ions, increase the solid-phase transmission rate of active ions, and further improve the internal diffusion kinetics of the negative electrode active material, reduce the internal polarization of the negative electrode active material, and improve the fast charging performance, rate performance, and cycle performance of the secondary battery. In some embodiments, the surface of the composite particle is the first region having an irregular carbon structure.

[0030] In the present invention, the term "irregular carbon structure" refers to a carbon structure that has a very low degree of graphitization and is close to an amorphous form (or has no fixed shape and no periodic structural order). The term "ordered carbon structure" refers to a carbon structure that is highly graphitized or has a fixed shape and periodic structural order.

[0031] In the present invention, the "first region" can mean a region having a disordered carbon structure on the surface of a composite particle.

[0032] According to some embodiments of the present invention, the first region includes a first active material, and the first active material includes hard carbon and / or soft carbon. Compared to soft carbon, hard carbon has a larger d002 spacing and micropore content after heat treatment at 1000° C. or higher, and can provide more active ion release sites. In some embodiments, the first active material includes hard carbon.

[0033] According to some embodiments of the present invention, the second region comprises a second active material, the second active material comprising at least one of graphite, graphene, carbon nanotubes, lithium oxide, and transition metal oxide, hi some embodiments, the lithium oxide comprises at least one of a lithium transition metal composite oxide.

[0034] In the present invention, the "transition metal" includes at least one of chromium, manganese, iron, cobalt, nickel, copper, zinc, and titanium. In some embodiments, the lithium oxide includes lithium titanate. In some embodiments, the transition metal oxide includes at least one of triiron tetroxide, trimanganese tetroxide, manganese dioxide, and tricobalt tetroxide.

[0035] According to some embodiments of the present invention, the size of the second active material is 10nm-2000nm, for example, 10nm-1000nm. In the present invention, the size of the second active material has different meanings for different kinds of materials, for example, when the second active material is a graphene material, the size corresponds to the average sheet diameter of the graphene material, when the second active material is a carbon nanotube material, the size corresponds to the average diameter of the carbon nanotube material, when the second active material is a graphite material, lithium oxide, or transition metal oxide, the size corresponds to its average particle size. That is, according to some embodiments of the present invention, the average particle size of graphite is 10 nm to 1000 nm, the average sheet diameter of graphene is 10 nm to 2000 nm, the average diameter of carbon nanotubes is 10 nm to 2000 nm, the average particle size of lithium oxide is 10 nm to 1000 nm, and the average particle size of transition metal oxide is 10 nm to 1000 nm, and preferably, the average particle size of graphite is 20 nm to 300 nm, the average sheet diameter of graphene is 20 nm to 500 nm, the average diameter of carbon nanotubes is 20 nm to 500 nm, the average particle size of lithium oxide is 20 nm to 300 nm, and the average particle size of transition metal oxide is 20 nm to 300 nm. Here, the average diameter of carbon nanotubes means the average diameter of the outer diameter of carbon nanotubes. Since active ions are more easily diffused in the second region having an ordered structure, the diffusion coefficient of active ions in the negative electrode active material can be improved by increasing the contact area between the first region and the second region. If the size of the second active material is too large, the contact area between the first and second regions will be small, which is unfavorable to the diffusion of active ions. If the size of the second active material is too small, the active material will be easily aggregated, which will affect the rate performance, fast charging performance and cycle performance of the secondary battery.

[0036] In some embodiments, the average particle size of the graphite can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or a range consisting of any two of these values.

[0037] In some embodiments, the average sheet diameter of graphene can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, or a range consisting of any two of these values.

[0038] In some embodiments, the average diameter of the carbon nanotubes can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, or a range consisting of any two of these values.

[0039] In some embodiments, the average particle size of the lithium oxide can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or a range consisting of any two of these values.

[0040] In some embodiments, the average particle size of the transition metal oxide can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or a range consisting of any two of these values.

[0041] According to some embodiments of the present invention, the second region has a random distribution or a layered distribution inside the composite particle. In some embodiments, the layered distribution is a single layer distribution or a multi-layer distribution, and the multi-layer distribution is, for example, a two-layer distribution, a three-layer distribution, or a four-layer distribution. The different distribution manners of the second region inside the composite particle can effectively reduce the free path of active ions, increase the solid-phase transmission rate of active lithium ions, reduce the internal polarization of the negative electrode active material, and further improve the rate performance, fast charging performance and cycle performance of the secondary battery.

[0042] According to some embodiments of the present invention, the composite particles are primary particles. In some embodiments, the particle size of the composite particles satisfies 3 μm≦Dv50≦12 μm. In some embodiments, Dv50 may be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or a range consisting of any two of these values. In the present invention, Dv50 means that in the volume-based particle size distribution of the composite particles, 50% of the particles have a particle size smaller than this value. If the particle size of the composite particles is too large, the wetting effect of the electrolyte is poor. If the particle size of the composite particles is too small, the specific surface area becomes large, and many SEI films are formed on the surface of the composite particles during the first charge, which increases the consumption of active ions and affects the cycle performance and rate performance of the secondary battery.

[0043] According to some embodiments of the present invention, the X-ray photoelectron spectroscopy spectrum of the negative electrode active material has a characteristic peak in the range of binding energy from 283 eV to 288 eV. In the present invention, the characteristic peak having a binding energy in the range of 283 eV to 288 eV corresponds to a characteristic peak of the disordered carbon structure in the first region.

[0044] According to some embodiments of the present invention, the negative electrode active material has an ID / IG ratio of 0.6 to 1.3, and ID is a Raman shift of 1300 cm -1 ~1400cm -1 IG represents the peak intensity in the range where the Raman shift is 1550 cm -1 ~1650cm -1 The peak intensity in the range is expressed as:

[0045] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in the 2θ range of 18° to 30°. In the present invention, the characteristic peak in the X-ray diffraction spectrum of the negative electrode active material in the 2θ range of 18° to 30° corresponds to the disordered carbon structure in the first region. In some embodiments, the half-width of the characteristic peak is 4° to 12°.

[0046] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in the 2θ range of 26° to 27°. In the present invention, the characteristic peak in the 2θ range of 26° to 27° in the X-ray diffraction spectrum of the negative electrode active material corresponds to graphite or carbon nanotubes (CNTs) having an ordered carbon structure in the second region.

[0047] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in at least one of the ranges of 2θ of 18° to 19°, 35° to 36°, and 43° to 44°. In the present invention, the characteristic peak in the X-ray diffraction spectrum of the negative electrode active material in the range of 2θ of 18° to 19°, 35° to 36°, or 43° to 44° corresponds to lithium titanate having an ordered structure in the second region. In some embodiments, the X-ray diffraction spectrum of the negative electrode active material has significant sharp peaks at 2θ of 18.4°, 35.7°, and 43.3°, and these significant sharp peaks correspond to lithium titanate having an ordered structure in the second region.

[0048] According to some embodiments of the present invention, the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in at least one of the following ranges of 2θ: 30° to 31°, 35° to 36°, 42.5° to 43.5°, 56.5° to 57.5°, and 62° to 63°. In the present invention, the characteristic peak in the X-ray diffraction spectrum of the negative electrode active material in the range of 2θ: 30° to 31°, 35° to 36°, 42.5° to 43.5°, 56.5° to 57.5°, or 62° to 63° corresponds to triiron tetroxide having an ordered structure in the second region. In some embodiments, the X-ray diffraction spectrum of the negative electrode active material has significant sharp peaks at 2θ: 30.2°, 35.5°, 43.1°, 57.1°, and 62.6°, and these significant sharp peaks correspond to triiron tetroxide having an ordered structure in the second region.

[0049] According to some embodiments of the present invention, the specific surface area of ​​the negative electrode active material is less than 1 m 2 / g~50m 2 / g. In some embodiments, the specific surface area of ​​the negative electrode active material is 2.5 g / cm 2 , 3g / cm 2 , 4g / cm 2 , 5g / cm 2 , 6g / cm 2 , 7g / cm 2 , 8g / cm 2 , 9g / cm 2 , 10g / cm2 , 12g / cm 2 , 15g / cm 2 , 20g / cm 2 , 25g / cm 2 , 30g / cm 2 , 35g / cm 2 , 40g / cm 2 , 45g / cm 2 In some embodiments, the specific surface area of ​​the negative electrode active material is 2 m 2 / g~10m 2 / g. If the specific surface area of ​​the negative electrode active material is too high, a large amount of SEI film is likely to be formed on its surface during the initial charge / discharge process of the secondary battery, which will cause the capacity loss of the secondary battery; at the same time, the negative electrode active material with a high specific surface area requires the addition of more binder to the negative electrode active material layer, which will increase the internal resistance of the negative electrode active material layer and affect the fast charging performance of the secondary battery.

[0050] According to some embodiments of the present invention, the negative electrode active material may further include other negative electrode active materials in addition to the composite particles. The specific type of the other negative electrode active materials is not particularly limited and may be selected according to the purpose. Examples of the other negative electrode active materials include soft carbon such as natural graphite or artificial graphite, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, and Li4Ti5O having a spinel structure. 12 , Li-Al alloy, but is not limited thereto.

[0051] II. Preparation method of composite particles The method for preparing the negative electrode active material provided by the present invention includes the following steps: S1: Mixing a second active material forming a second region, a resin, a solvent, and an optional hardener to obtain a first mixture. S2: A step of drying the first mixed liquid by spray drying or the like to obtain a precursor A containing a second active material. S3: Mixing precursor A with a resin, a solvent and an optional hardener to obtain a second mixture. S4: A step of drying the second mixed liquid by spray drying or the like to obtain precursor B. S5: A step of carbonizing the precursor B to obtain the composite particles.

[0052] According to some embodiments of the present invention, in S1, the mass ratios of the second active material, the resin, the solvent, and the curing agent, a1:a2:a3:a4, are 0.01 to 0.6 for a1:a2, 0.2 to 3 for a3:a2, and 0 to 0.5 for a4:a2. In some embodiments, the mixing in S1 includes adding the second active material forming the second region to the solvent and dispersing it under ultrasonic waves for, for example, 1h to 3h, and then adding the resin and the curing agent in this order and mixing it under a stirrer for, for example, 0.5h to 3h.

[0053] According to some embodiments of the present invention, in S3, the mass ratios b1:b2:b3:b4 of precursor A, resin, solvent, and curing agent are such that b2:b1 is 0.3 to 5, b3:b2 is 0.2 to 7, and b4:b2 is 0 to 0.5.

[0054] The method for preparing the composite particles provided by the present invention further includes the following steps: M1: Mixing a second active material forming a second region, a resin, a solvent, hard carbon, and an optional curing agent to obtain a first mixture. M2: A step of drying the first mixed liquid by spray drying or the like to obtain a precursor A1 containing a second active material. M3: Mixing precursor A1 with a resin, a solvent and an optional hardener to obtain a second mixture. M4: A step of drying the second mixed liquid by spray drying or the like to obtain a precursor B1. M5: A step of carbonizing the precursor B1 to obtain the composite particles.

[0055] The method for preparing the composite particles provided by the present invention further includes the following steps: N1: Mixing a second active material forming a second region, a resin, a solvent, hard carbon, and an optional curing agent to obtain a first mixture. N2: A step of drying the first mixed liquid by spray drying or the like to obtain a precursor A2. N3: Mixing precursor A2 with a resin, a solvent and an optional hardener to obtain a second mixture. N4: A step of drying the second mixed liquid by spray drying or the like to obtain a precursor B2. N5: Mixing precursor B2, a resin, a solvent, a second active material, and an optional curing agent to obtain a third mixture. N6: A step of drying the third mixed liquid by spray drying or the like to obtain a precursor C. N7: Mixing precursor C with a resin, a solvent and an optional hardener to obtain a fourth mixture. N8: A step of drying the fourth mixed liquid by spray drying or the like to obtain a precursor D. N9: Optionally, steps N5 to N8 are repeated at least once to obtain a precursor E. N10: Carbonizing the precursor D or E to obtain the composite particles.

[0056] According to some embodiments of the present invention, in M1 and N1, the mass ratios c1:c2:c3:c4:c5 of the second active material, resin, solvent, curing agent, and hard carbon are c1:c2 is 0.01 to 3, c3:c2 is 0.2 to 7, c4:c2 is 0 to 0.5, and c5:c2 is 1 to 15. According to some embodiments of the present invention, in N5, the mass ratios d1:d2:d3:d4:d5 of the second active material, resin, solvent, curing agent, and precursor are d1:d2 is 0.01 to 3, d3:d2 is 0.2 to 7, d4:d2 is 0 to 0.5, and d5:d2 is 1 to 20. In some embodiments, the mixing in M1, N1 and N5 includes adding the second active material forming the second region to a solvent and dispersing it under ultrasonic waves for, for example, 1h to 3h, followed by adding the resin, curing agent, hard carbon, or precursor in that order and mixing under a stirrer for 0.5h to 3h.

[0057] According to some embodiments of the present invention, in M3, N3 and N7, the mass ratios of precursor, resin, solvent and hardener, e1:e2:e3:e4, are such that e2:e1 is 0.1-1, e3:e2 is 0.5-3 and e4:e2 is 0-0.5.

[0058] According to some embodiments of the present invention, the intake air temperature is set to 130°C to 300°C, and the exhaust air temperature is set to 50°C to 150°C during spray drying.

[0059] According to some embodiments of the present invention, the carbonization includes a first carbonization and a second carbonization performed sequentially under an inert atmosphere. In some embodiments, the temperature of the first carbonization is 250°C to 650°C. In some embodiments, the time of the first carbonization is 1h to 4h. In some embodiments, the temperature of the second carbonization is 700°C to 1600°C. In some embodiments, the time of the second carbonization is 1h to 12h.

[0060] According to some embodiments of the present invention, the resin comprises at least one of resole resin, epoxy resin, vinyl resin, bismaleimide resin, thermosetting polyimide resin, and cyanate ester resin. In some embodiments, the solvent comprises at least one of water, ethanol, methanol, acetone, dichloromethane, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylformamide, and the specific solvent selection is determined by the resin selected. In some embodiments, the hardener comprises at least one of vinyltriamine, aminoethylpiperazine, m-phenylenediamine, diaminodiphenylmethane, and hexamethylenetetramine. In some embodiments, no hardener may be used, and the specific selection is determined by the resin system selected.

[0061] 3. Secondary battery The secondary battery provided by the present invention includes a negative electrode including a negative electrode active material layer and a current collector, and the negative electrode active material layer includes the negative electrode active material of the first embodiment.

[0062] According to some embodiments of the present invention, the porosity of the negative electrode active material layer is 10% to 50%. In some embodiments, the porosity of the negative electrode active material layer may be 15%, 20%, 25%, 30%, 35%, 40%, 45%, or a range consisting of any two of these values. In some embodiments, the porosity of the negative electrode active material layer is 15% to 35%. When the porosity of the negative electrode active material layer is in the above range, the rate performance, rapid charging performance, and cycle performance of the secondary battery can be further improved. If the porosity of the negative electrode active material layer is too large, the number of contact points between the negative electrode active material particles decreases, and the internal resistance of the secondary battery increases. If the porosity of the negative electrode active material layer is too small, the wettability of the electrolyte will be poor, the transport path of the active ions will be long, and the shuttle of the active ions between the positive and negative electrodes will be hindered. The negative electrode pieces that are not in contact with the electrolyte will be unable to participate in the electrochemical reaction inside the secondary battery. At the same time, the interface resistance of the secondary battery will increase, affecting the rate performance, cycle performance, discharge capacity and service life of the secondary battery.

[0063] In some embodiments, the adhesive strength between the negative electrode active material layer and the current collector is 3N / m to 30N / m, for example, 5N / m, 10N / m, 15N / m, 20N / m, or 25N / m. When the adhesive strength between the negative electrode active material layer and the current collector is in this range, the rate performance, rapid charging performance, and cycle performance of the secondary battery can be further improved. If the adhesive strength between the negative electrode active material layer and the current collector is too low, peeling and burrs are likely to occur in the roll press and slit process, resulting in safety problems for the secondary battery. If the adhesive strength between the negative electrode active material layer and the current collector is too high, the adhesive strength between the active material and the current collector is too large, the proportion of the binder is high, the internal resistance of the secondary battery is likely to be high, the dynamic loss is serious, and the attenuation of the long cycle performance is accelerated.

[0064] In some embodiments, the negative electrode current collector comprises copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0065] In some embodiments, the negative electrode active material layer further includes a binder and a conductive agent. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, or nylon.

[0066] In some embodiments, the conductive agent includes, but is not limited to, a carbon-based material, a metal-based material, a conductive polymer, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, and any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, and silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0067] The negative electrode of the present invention may be prepared by a method known in the art. In general, the negative electrode active material and materials such as optional conductive agents (e.g., carbon-based materials such as carbon black and metal particles), binders (e.g., SBR) and other optional additives (e.g., PTC thermistor materials) are mixed and dispersed in a solvent (e.g., deionized water), uniformly stirred, and then uniformly applied to a negative electrode current collector, and dried to obtain a negative electrode.

[0068] The secondary battery of the present invention further includes a positive electrode including a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material, a binder, and a conductive agent.

[0069] According to some embodiments of the present invention, the positive electrode current collector can be a metal foil piece or a composite current collector. For example, the positive electrode current collector can be an aluminum foil. The composite current collector can be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer substrate.

[0070] According to some embodiments of the present invention, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminate, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron siliconate, lithium vanadium siliconate, lithium cobalt siliconate, lithium manganese siliconate, lithium manganese spinel type lithium manganate, lithium nickel manganate spinel type, and lithium titanate. In some embodiments, the binder includes at least one adhesive polymer, for example, polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethylcellulose, lithium carboxymethylcellulose, modified polyvinylidene fluoride, modified SBR rubber, and polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol, and polyacrylic acid. In some embodiments, the conductive agent includes a carbon-based material such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, or carbon fiber, a metal-based material such as a metal powder or metal fiber, for example, copper, nickel, aluminum, silver, etc., a conductive polymer such as a polyphenylene derivative, or a mixture thereof.

[0071] The positive electrode of the present invention may be prepared by a method known in the art. In general, the positive electrode active material, the conductive material, and the adhesive are mixed, dispersed in a solvent, and uniformly stirred, and then coated on a positive electrode current collector and dried to obtain a positive electrode. In some embodiments, the solvent includes, but is not limited to, N-methylpyrrolidone. The secondary battery of the present invention further includes a separator, and the material and shape of the separator used in the secondary battery of the present invention are not particularly limited and may be any of the techniques disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic material formed from a material stable to the electrolyte of the present invention.

[0072] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, film, or composite film having a porous structure, and the material of the substrate layer is at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, the substrate layer may be selected from a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane.

[0073] A surface treatment layer is provided on at least one surface of the base layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer obtained by mixing a polymer and an inorganic material. The inorganic layer contains inorganic particles and a binder, and the inorganic particles are at least one selected from the group consisting of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium oxide, tin oxide, cerium oxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is at least one selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinylalkoxy, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer includes a polymer, and the polymer material is at least one selected from the group consisting of polyamide, polyacrylonitrile, acrylic ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinylalkoxy, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0074] The secondary battery of the present invention further comprises an electrolyte. The electrolyte used in the present invention may be any electrolyte known in the art.

[0075] According to some embodiments of the present invention, the electrolyte comprises an organic solvent, a lithium salt, and an optional additive. The organic solvent in the electrolyte of the present invention may be any organic solvent known in the art that can be used as a solvent in an electrolyte. The electrolyte used in the electrolyte of the present invention is not particularly limited and may be any electrolyte known in the art. The additive in the electrolyte of the present invention may be any additive known in the art that can be used as an additive in an electrolyte. In some examples, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate. In some examples, the organic solvent includes an ether solvent, such as at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some examples, the lithium salt includes at least one of an organic lithium salt and an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonimide) LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalato)borate LiB(C2O4)2 (LiBOB), or lithium difluoro(oxalato)borate LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0076] According to some embodiments of the present invention, the secondary battery of the present invention includes, but is not limited to, a lithium ion battery or a sodium ion battery. In some examples, the secondary battery includes a lithium ion battery.

[0077] 4.Electronic equipment The present invention further provides an electronic device comprising the secondary battery according to the third aspect of the present invention.

[0078] The electronic device or apparatus of the present invention is not particularly limited. In some embodiments, the electronic device of the present invention includes, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, liquid crystal televisions, portable cleaners, portable CD players, minidisks, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, auxiliary bicycles, bicycles, lighting equipment, toys, game machines, clocks, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors.

[0079] In the following examples and comparative examples, reagents, materials and equipment used are commercially available unless otherwise stated.

[0080] Examples and Comparative Examples Example 1 Preparation of positive electrode pieces The positive electrode active materials lithium cobalt oxide, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred uniformly to obtain a slurry. The slurry (solid content 72 wt%) was uniformly coated on aluminum foil, the positive electrode current collector, to a thickness of 80 μm, dried at 85 ° C, and then cold pressed, cut, and cut, and then dried in a vacuum at 85 ° C for 4 hours to obtain a positive electrode piece.

[0081] Preparation of negative electrode pieces Composite particles, binder styrene butadiene rubber and sodium carboxymethylcellulose (CMC) were dissolved in deionized water in a weight ratio of 97:1.5:1.5 to form a negative electrode slurry (solid content 40wt%). A 10μm thick copper foil was used as a negative electrode current collector, and the negative electrode slurry was applied to the negative electrode current collector to a thickness of 50μm, dried at 85℃, cold pressed, cut, and then dried under vacuum conditions at 120℃ for 12 hours to obtain a negative electrode piece.

[0082] Here, the composite particles were prepared in the following steps: Nanographite microbeads with an average particle size of 100 nm, resol resin, ethanol, and hexamethylenetetramine were mixed in a mass ratio of 10:100:100:5 to prepare a mixed solution (first, the nanographite microbeads, which are the second active material, were added to an ethanol solvent and dispersed by ultrasonic waves for 2 hours, then the resol resin and hexamethylenetetramine were added in this order and mixed with a stirrer for 1 hour), and then the mixed solution was spray-dried, and the inlet air temperature was set to 200°C and the exhaust temperature to 130°C during spraying to obtain a precursor A containing the second active material. The precursor A obtained after the primary spraying, phenol resin, ethanol, and hexamethylenetetramine were mixed in a mass ratio of 100:50:50:5 to prepare a mixed solution (precursor A was mixed with phenol resin, ethanol, and hexamethylenetetramine in a stirrer for 1 h), and then the mixed solution was spray-dried. The inlet air temperature was set to 200°C and the exhaust temperature was set to 130°C during spraying to obtain precursor B. Precursor B was pre-carbonized in a nitrogen gas atmosphere at 600°C for 1.5 h, and then carbonized in a nitrogen gas atmosphere at 1100°C for 2 h to obtain composite particles having a structure similar to that shown in the left diagram of FIG. 6, in which the second active material was nanographite and the nanographite was randomly distributed inside the composite particles.

[0083] Preparation of the Separator The separator was polyethylene (PE) with a thickness of 7 μm.

[0084] Preparation of electrolyte solution In a glove box with a dry argon gas atmosphere, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC:PC:DEC=1:1:1, and then lithium salts LiPF6 and fluoroethylene carbonate were added and mixed uniformly to obtain an electrolyte solution. Here, based on the mass of the electrolyte solution, the mass percentage of LiPF6 was 12.5% ​​and the mass percentage of fluoroethylene carbonate was 5%. Preparation of Lithium-Ion Battery Positive electrode pieces, separators, and negative electrode pieces are stacked in this order, and a separator is placed between the positive electrode pieces and the negative electrode pieces to serve as an insulator. The stack is then wound up to obtain an electrode assembly. The electrode assembly is placed in an aluminum laminate exterior, and moisture is removed at 80°C. The electrolyte is then injected and sealed, and a lithium-ion battery is obtained through processes such as formation, degassing, and trimming.

[0085] Example 2 Example 2 had the same parameters as Example 1, except that the second active material in the composite particles was graphene.

[0086] Example 3 Example 3 had the same parameters as Example 1, except that the second active material in the composite particles was carbon nanotubes.

[0087] Example 4 In Example 4, the parameters were the same as in Example 1, except that the second active material in the composite particles was lithium titanate. As shown in Figure 1, the composite particles obtained in this example were observed to have clearly distinct lattice fringes under a high-resolution transmission electron microscope after ultrathin sectioning. Here, the irregularly stacked regions were lattice fringes of an irregular carbon structure in the first region in the composite particles, and the regularly stacked regions were lattice fringes of an ordered structure in the second region in the composite particles.

[0088] As shown in FIG. 2, when the cross section of the negative electrode piece containing the composite particles obtained in this example was observed with a scanning electron microscope, it was found that the dark gray parts were hard carbon, the light gray parts were lithium titanate particles, and the lithium titanate particles were randomly distributed inside the composite particles.

[0089] As shown in FIG. 3, the carbon fine spectrum of the X-ray photoelectron spectroscopy spectrum of the composite particle obtained in this example had a characteristic peak in the range of 283 eV to 288 eV that corresponds to the disordered carbon structure in the first region.

[0090] As shown in FIG. 4, in the Raman spectrum of the composite particles obtained in this example, ID / IG is about 0.7, and ID is 1300 cm -1 ~1400cm -1 represents the peak intensity in the range of 1550 cm -1 ~1650cm -1 represents the peak intensity in the range.

[0091] As shown in Figure 5, the XRD spectrum of the composite particles obtained in this example had sharp characteristic peaks in the ranges of 8° to 19°, 35° to 36°, and 43° to 44° corresponding to lithium titanate having an ordered structure in the second region.

[0092] Example 5 Example 5 had the same parameters as Example 1, except that the second active material in the composite particles was iron oxide.

[0093] Comparative Example 1 In Comparative Example 1, the parameters were the same as those of Example 1, except that no second active material was added during the preparation of the composite particles, which were pure hard carbon materials.

[0094] Comparative Example 2 In Comparative Example 2, the negative electrode active material was artificial graphite.

[0095] Example 6 Example 6 had the same parameters as Example 1, except that the second active material in the composite particles was graphite with an average particle size of 30 nm.

[0096] Example 7 Example 7 had the same parameters as Example 1, except that the second active material in the composite particles was graphite with an average particle size of 300 nm.

[0097] Example 8 Example 8 had the same parameters as Example 1, except that the second active material in the composite particles was graphite with an average particle size of 500 nm.

[0098] Example 9 Example 9 had the same parameters as Example 1, except that the second active material in the composite particles was graphite with an average particle size of 1000 nm.

[0099] Example 10 The preparation method of the composite particles of Example 10 was as follows: Nano-lithium titanate microbeads with an average particle size of 100 nm, resol resin, ethanol, hexamethylenetetramine and hard carbon microbeads with Dv50 of 8 μm were mixed in a mass ratio of 10:10:50:1:100 to prepare a mixed solution (first, the nano-lithium titanate microbeads, which are the second active material, were added to ethanol and dispersed by ultrasonic waves for 2 hours, then the resol resin, hexamethylenetetramine and hard carbon microbeads were added in this order and mixed with a stirrer for 1 hour), then the mixed solution was spray-dried, and the inlet air temperature was set to 200°C and the exhaust temperature was set to 130°C during spraying to obtain a precursor A1 containing the second active material. The precursor A1 obtained after the primary spraying, resol resin, ethanol, and hexamethylenetetramine were mixed in a mass ratio of 100:50:50:5 to prepare a mixed solution (first, the precursor A1 was mixed with the resol resin, ethanol, and hexamethylenetetramine in a stirrer for 1 h), then the mixed solution was spray-dried, and the inlet air temperature was set to 200 ° C and the exhaust temperature was set to 130 ° C during spraying to obtain precursor B1. Precursor B1 was pre-carbonized in a nitrogen gas atmosphere at 600 ° C for 1.5 h, and then carbonized in a nitrogen gas atmosphere at 1100 ° C for 2 h to obtain composite particles having a structure similar to that of the center diagram of FIG. 6, in which the second active material is nano-lithium titanate, and the nano-lithium titanate is distributed in layers inside the composite particles.

[0100] Example 11 The preparation concept of the composite particles of Example 11 was similar to that of Example 10, and was specifically as follows: Nano-lithium titanate microbeads with an average particle size of 100 nm, resol resin, ethanol, hexamethylenetetramine and hard carbon microbeads with Dv50 of 5 μm were mixed in a mass ratio of 10:10:50:1:100 to prepare a mixed solution (first, the nano-lithium titanate microbeads, which are the second active material, were added to ethanol and dispersed by ultrasonic waves for 2 hours, then the resol resin, hexamethylenetetramine and hard carbon microbeads were added in this order and mixed with a stirrer for 1 hour), and then the mixed solution was spray-dried, and the inlet air temperature was set to 200 ° C. and the exhaust temperature was set to 130 ° C. during spraying, to obtain a precursor A2 containing the second active material. The precursor A2 obtained after the primary spraying, resol resin, ethanol, and hexamethylenetetramine were mixed in a mass ratio of 100:25:25:2.5 to prepare a mixed solution (precursor A2 was mixed with resol resin, ethanol, and hexamethylenetetramine in a stirrer for 1h), and then the mixed solution was spray-dried, and the inlet air temperature was set to 200°C and the exhaust temperature to 130°C during spraying to obtain precursor B2. The precursor B2 obtained after the secondary spraying, nano lithium titanate microbeads with an average particle size of 100 nm, resol resin, ethanol, and hexamethylenetetramine were mixed in a mass ratio of 100:10:10:50:1 to prepare a mixed solution, and the mixing process and spray-drying process were repeated to obtain precursor C. The precursor C obtained after the third spraying was mixed with resol resin, ethanol, and hexamethylenetetramine in a mass ratio of 100:25:25:2.5 to prepare a mixed solution, and the mixing process and spray drying process were repeated to obtain precursor D. Precursor D was carbonized under conditions similar to those in Example 10 to obtain composite particles having a structure similar to that shown in the right diagram of Figure 6, in which the second active material is nano-lithium titanate, and the nano-lithium titanate is distributed in a two-layer shape inside the composite particles.

[0101] Example 12 The preparation method of the composite particles of Example 12 was as follows. Nano-lithium titanate microbeads with an average particle size of 100 nm, resol resin, ethanol, hexamethylenetetramine, and hard carbon microbeads with a Dv50 of 12 μm were mixed in a mass ratio of 10:5:50:0.5:100 to prepare a mixed solution (first, the nano-lithium titanate microbeads were added to ethanol and dispersed with ultrasonic waves for 2 hours, then the resol resin, hexamethylenetetramine, and hard carbon microbeads were added in this order and mixed with a stirrer for 1 hour), and then the mixed solution was spray-dried, and the inlet air temperature was set to 200° C. and the exhaust air temperature was set to 130° C. during spraying, to obtain a precursor E. After the precursor E was carbonized under conditions similar to those of Example 10, a composite particle in which the active material was nano-lithium titanate and the nano-lithium titanate was adsorbed and distributed on the hard carbon surface was obtained.

[0102] Measurement method

[0103] Measurement of relevant parameters of negative electrode active material A fully discharged lithium ion battery was taken out, disassembled, and the negative electrode was taken out. It was then immersed in DMC (ethylene carbonate) for 20 minutes, and then washed once each with DMC and acetone in order to remove the electrolyte and the surface SEI film. It was then placed in an oven and baked at 80 ° C for 12 hours to obtain a treated negative electrode piece. The powder in the negative electrode piece was scraped off with a doctor blade, and the scraped powder was heat-treated in a tubular furnace at 400 ° C for 4 hours in an argon gas atmosphere to remove the binder attached to the surface of the negative electrode active material, and the negative electrode active material was obtained. The following measurements were performed on the obtained negative electrode active material layer and negative electrode active material.

[0104] 1. TEM After the negative electrode active material was encapsulated in epoxy resin and cured, the material was cut into pieces of 50-70 nm size using ultrathin sectioning to prepare samples. A high-magnification transmission electron microscope was used to select and observe the cross sections of the particle samples to observe the distribution of long-range regularly arranged regions, i.e., second regions, and amorphous regions (where there is no long-range ordered sheet layer and the sheet layer arrangement is random), i.e., first regions.

[0105] 2. SEM The process of preparing samples by cross-sectioning the negative electrode The negative electrode pieces after the above treatment were cut into pieces of 0.5cm x 1cm in size, and the cut negative electrode was attached to a silicon wafer carrier of 1cm x 1.5cm in size using a conductive adhesive, and then one end of the negative electrode pieces was treated with argon ion polishing (accelerating voltage 8KV, 4 hours / sample). Here, argon ion polishing uses a high voltage electric field to ionize argon gas to generate an ion state, and the generated argon ions collide with the surface of the negative electrode at high speed under the action of the accelerating voltage, peeling off the negative electrode pieces layer by layer to achieve the polishing effect. The scanning electron microscope used in this invention was a JEOL JSM-6360LV model and associated energy dispersive X-ray spectrometer, which was used to analyze the cross-sectional topographic structure and element distribution of the polished negative electrode pieces and to observe the distribution of the second and first regions within the negative electrode active material.

[0106] 3. Surface defects The surface defect level of the negative electrode active material was measured using a laser microscope confocal Raman spectrometer, and the 1350 cm -1 Peak intensity at ID and 1580 cm -1 The surface defectivity of the samples was characterized using the ratio of the peak intensity I D / I G at the potential. Each sample was measured at multiple potentials, and the uniformity of the surface defectivity in different regions was characterized by the standard deviation of these measurements. The average value and standard deviation of I D / I G of the negative active material were obtained by taking the unsieved negative active material, measuring 100 points, obtaining the corresponding I D / I G values, and calculating the average value and standard deviation of the 100 values.

[0107] 4. X-ray diffraction (XRD) The negative electrode active material was measured using an X-ray powder diffractometer (XRD, instrument model number: Bruker D8 ADVANCE), the target was Cu Kα, the voltage current was 40 KV / 40 mA, the scanning angle was in the range of 5° to 80°, the scanning step width was 0.00836°, and the time for each step width was 0.3 s.

[0108] 5. X-ray photoelectron spectroscopy (XPS) The powder sample was subjected to XPS full spectrum scanning to determine the spectral peaks of C1s, O1s, C(KLL), and O(KLL), and then the chemical shifts of titanium, oxygen, and iron elements were measured using high-resolution spectra, with a scan width of 10 eV to 30 eV. Charge calibration was required for the binding energy of the elements, and generally C (285 eV), O (532 eV) or a fixed internal standard element were used to calibrate the charge amount. Finally, the results obtained were fitted using Xpeak software to obtain the results.

[0109] 6. Particle size of negative electrode active material particles The particle size of the negative electrode active material particles was measured using a Malvern particle size analyzer. The negative electrode active material was dispersed in ethanol, which is a dispersant, and ultrasonically treated for 30 minutes. The sample was then placed in the Malvern particle size analyzer to measure the Dv50 of the negative electrode active material particles.

[0110] 7. Specific surface area of ​​negative electrode active material particles The specific surface area of ​​the negative active material was measured by a nitrogen adsorption / desorption method using a specific surface area analyzer (Tristar II 3020M). Specifically, the sample of the negative active material was dried in a vacuum drying oven, placed in a sample tube, and measured using the specific surface area analyzer.

[0111] 8. Gram capacity of negative electrode active material The negative electrode active material was mixed, coated, and dried to prepare a negative electrode piece, and the lithium sheet was used as the positive electrode, assembled into a button battery, and then measured. The button battery was discharged at 0.05C to 5.0mV, discharged at 50μA to 5.0mV, discharged at 10μA to 5.0mV, and charged at 0.1C to 2.0V, and the capacity of the button battery at this time was recorded and expressed as gram capacity.

[0112] Measurement of relevant parameters of negative electrode pieces 9. Porosity of negative electrode active material layer The treated negative electrode pieces were prepared into perfect circular pieces. For each Example or Comparative Example, 30 samples were measured, and the volume of each sample was approximately 0.35 cm 3 The porosity of the negative electrode active material layer was measured according to "GB / T24586-2009 Measurement of apparent density, true density, and porosity of iron ore."

[0113] 10. Binding strength The brand of the equipment used to measure the adhesive strength between the negative electrode active material layer and the negative electrode current collector was Instron, model number 33652. The treated negative electrode piece (width 30 mm × length (100 mm to 160 mm)) was taken and fixed to a steel plate with double-sided tape (model number: 3M9448A, width 20 mm × length (90 mm to 150 mm)), and a paper tape of the same width as the negative electrode piece was fixed to one side of the negative electrode piece with tape, the limit block of the tensile machine was adjusted to an appropriate position, the paper tape was folded back upward and slid 40 mm, the sliding speed was 50 mm / min, and the adhesive strength between the negative electrode active material layer and the negative electrode current collector was measured at 180° (i.e., stretched in the opposite direction).

[0114] 11. Compression density of negative electrode pieces A certain area S of the treated negative electrode piece (both sides of the negative electrode current collector coated with the negative electrode active material layer) was weighed with an electronic balance and designated as W1, and the thickness T1 of the negative electrode piece was measured with a micrometer. The negative electrode active material layer was washed off using a solvent and dried, and the weight of the negative electrode current collector was measured and designated as W2, and the thickness T2 of the negative electrode current collector was measured with a micrometer. The weight W0 and thickness T0 of the negative electrode active material layer disposed on one side of the negative electrode current collector, and the compressed density of the negative electrode active material layer were calculated using the following formulas. W0=(W1-W2) / 2; T0=(T1-T2) / 2; Compressed density=W0 / (T0×S).

[0115] Measurement of relevant parameters of lithium-ion batteries 12. Energy density of lithium-ion batteries Five sets of lithium ion batteries prepared in all comparative examples and examples were taken, and the average value was calculated. First, the first charge and discharge were performed at 25°C, and constant current charging and constant voltage charging were performed at a charge current of 0.5C until the upper limit voltage reached 4.48V, and then constant current discharging was performed at a discharge current of 0.2C until the discharge end voltage reached 3V, and the energy density improvement percentage of each example and comparative example relative to Comparative Example 2 was calculated.

[0116] 13. Cycle performance of lithium-ion batteries Five sets of lithium ion batteries prepared in all the comparative examples and examples were taken, and the average value was calculated. The lithium ion batteries were repeatedly charged and discharged in the following steps, and the cycle capacity retention rate and cycle thickness expansion rate of the lithium ion batteries were calculated. First, the lithium-ion battery was charged and discharged for the first time at 25°C. It was then charged at a constant current of 1C until the upper voltage reached 4.48V, after which it was converted to a constant voltage charge, and then discharged at a constant current of 1C until the final voltage reached 3V. The discharge capacity of the first cycle and the thickness of the fully charged lithium-ion battery were recorded, and then 400 charge / discharge cycles were performed, and the discharge capacity of the 400th cycle and the thickness of the fully charged lithium-ion battery were recorded. Cycle capacity retention rate = (discharge capacity at 400th cycle / discharge capacity at first cycle) x 100% Cycle thickness expansion rate = (thickness of fully charged lithium-ion battery at 400th cycle / thickness of fully charged lithium-ion battery at first cycle) x 100%

[0117] 14. Lithium-ion battery charging rate performance Five lithium-ion batteries from each set were taken, and the batteries were repeatedly charged and discharged according to the following steps. The capacity (average value) at each charging stage was recorded, and the percentage of the CC segment capacity was calculated. The specific steps were as follows. First, the lithium-ion battery was left in an environment of 25°C for 1 hour. The battery was charged with constant current (CC) at a charge rate of 1C, and then converted to constant voltage (CV) charging after charging to 4.48V. When the charging current was lower than 0.05C, charging was stopped and the battery was left for 5 minutes. In order to ensure the integrity of the subsequent charge and discharge process, the battery was discharged at a constant current of 0.2C to 3V and left for 5 minutes. Next, the battery was fully charged according to the previous CC+CV charging mode at different rates such as 0.2C, 0.5C, 1C, 2C, and 3C, and after leaving it for 5 minutes, the battery capacity was fully discharged at a rate of 0.2C. Here, each rate was cycled once. The percentage of the CC segment capacity at different charging rates was calculated. As shown in Table 2, the measurement was performed by fully charging the battery according to the previous CC+CV charging mode at a rate of 3C. The calculation formula was as follows: Percentage of CC segment capacity (3C) = [CC segment charge capacity / (CC+CV) total charge capacity] x 100%

[0118] 15. Electrochemical impedance spectroscopy (EIS) and lithium ion diffusion coefficient a) The preparation of the three-electrode battery and lithium plating were the same as those of the lithium-ion battery described above. In the preparation process of the lithium-ion battery, a copper wire was connected to the battery as a reference electrode, and the negative electrodes were lithium plated at a current of 20 μA for 6 h each. After the lithium plating was completed, EIS was measured at 25° C. b) The EIS measurement steps were as follows. The lithium-plated three-electrode battery was connected to a Bio-Logic VMP3B electrochemical workstation manufactured by Biologie, France, and measured. Here, the measurement frequency range was 30mHz to 50kHz, and the amplitude was 5mV. After collecting the data, the data was analyzed using an impedance complex plane diagram, and the impedance Rct data of the lithium-ion battery negative electrode was obtained. c) Under the action of low-frequency AC signals, the impedance of the battery is mainly determined by the mass transfer step, so the corresponding Warburg coefficient σ is calculated based on the AC impedance spectrum curve, and the differential value between the negative electrode potential and the battery charge state is calculated by coulometric titration.

number

[0119] The lithium ion diffusion coefficient of the corresponding battery charge state is calculated using the following formula:

number

[0120] can be calculated.

number

[0121] In the formula, V M is the average molar volume of the negative electrode active material, S is the effective area of ​​the negative electrode, F is the Faraday constant, and the Warburg coefficient σ is the Z'-ω of the EIS curve. -1 / 2 The slope value corresponding to Derivative value of negative electrode potential and battery charge state

number

[0122] The measurement method was as follows: the battery was charged at 0.1C, and after each 1-hour charge, it was left to stand for 2 hours, and after the voltage stabilized, the negative electrode open circuit voltage was measured to obtain a charging Coulomb titration curve. The present invention measured the lithium ion diffusion coefficient when the charge state of the lithium ion battery was 90%.

[0123] Measurement results Examples 1 to 5 and Comparative Examples 1 and 2 reflect the effects of the first and second regions on the performance of lithium-ion batteries, where the second regions are randomly distributed inside the composite particles, and the detailed data are as shown in Table 1.

[0124] [Table 1]

[0125] As can be seen from the comparison between Example 1 to Example 5 and Comparative Example 1, the lithium ion diffusion coefficients at 90% SOC of Example 1 to Example 5 are all higher than Comparative Example 1. This shows that the introduction of the second region with an ordered structure into the composite particles containing the first region with an irregular structure can effectively improve the lithium ion solid-phase diffusion coefficient at the late stage of lithium absorption, and the internal polarization is small, so that the fast charging performance, rate performance, and cycle performance of the lithium ion battery can be effectively improved. Since the second active material with an ordered structure has a higher density, the negative electrode pieces of Examples 1 to 5 can obtain a higher compression density than Comparative Example 1 in the cold pressing process, which ensures that the negative electrode has a higher capacity and improves the energy density of the lithium ion battery.

[0126] Examples 1, 6 to 9 show the effect of the average particle size of the second active material on the performance of a lithium ion battery, where the second active material is nanographite, which is randomly distributed inside the composite particles, and the detailed data are shown in Table 2.

[0127] [Table 2]

[0128] As can be seen from comparing Example 1 with Examples 6 to 9, the average particle size of the nanographite, which is the second active material introduced, affects the lithium ion diffusion coefficient at high SOC and the rapid charging capability of the lithium ion battery. Here, Example 1, in which the average particle size of the nanographite, which is the second active material, is 100 nm, has the largest lithium ion diffusion coefficient at high SOC, and at the same time, when charged at a rate of 3C, has the highest CC segment capacity and has better rapid charging capability.

[0129] Examples 4, 10 to 12 show the effect of the distribution of the second active material in the composite particles on the performance of the lithium ion battery, where the second active material is nano-lithium titanate, the average particle size of the second active material is 100 nm, and the detailed data are shown in Table 3.

[0130] [Table 3]

[0131] As can be seen from a comparison between Examples 4, 10, and 12, when the second active material is distributed randomly or in layers inside the composite particles, the lithium ion diffusion coefficient at high SOC can be effectively improved, and the fast charging performance, rate performance, and cycle performance of the secondary battery can be further improved.

[0132] Although several exemplary embodiments of the present invention have been disclosed and described, the present invention is not limited to the disclosed embodiments. Rather, those skilled in the art will recognize that various modifications and changes can be made to the described embodiments without departing from the spirit and scope of the present invention as set forth in the appended claims.

Claims

1. a composite particle comprising a first region and a second region, the first region having a disordered carbon structure and the second region having an ordered carbon structure and / or a metal oxide structure, the surface of the composite particle comprising the first region; the first region includes a first active material, the first active material includes hard carbon; the second region includes a second active material, the second active material including at least one of graphite, graphene, carbon nanotubes, lithium oxide, and transition metal oxide; The second active material is (6) The average particle size of the graphite is 20 nm to 300 nm; (7) The average sheet diameter of the graphene is 20 nm to 500 nm; (8) The average diameter of the carbon nanotubes is 20 nm to 500 nm; (9) The average particle size of the lithium oxide is 20 nm to 300 nm; (10) A negative electrode active material, characterized in that an average particle size of the transition metal oxide is 20 nm to 300 nm.

2. The negative electrode active material according to claim 1 , wherein the second regions are randomly or layeredly distributed within the composite particle.

3. The negative electrode active material according to claim 1 , wherein the composite particles are primary particles, and the particle diameter of the composite particles satisfies 3 μm≦Dv50≦12 μm.

4. The negative electrode active material is (a) the X-ray photoelectron spectroscopy spectrum of the negative electrode active material has a characteristic peak in the range of 283 eV to 288 eV; (b) the negative electrode active material has an ID / IG ratio of 0.6 to 1.3, where ID represents a peak intensity in a Raman shift range of 1300 cm-1 to 1400 cm-1 when a Raman spectrum is measured, and IG represents a peak intensity in a Raman shift range of 1550 cm-1 to 1650 cm-1 when a Raman spectrum is measured; (c) the specific surface area of ​​the negative electrode active material is 1 m2 / g to 50 m2 / g.

5. The negative electrode active material is (d) the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in the range of 18° to 30°, and the half-width of the characteristic peak is 4° to 12°; (e) the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in the range of 26° to 27°; (f) the X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in at least one range of 18° to 19°, 35° to 36°, and 43° to 44°; (g) an X-ray diffraction spectrum of the negative electrode active material has a characteristic peak in at least one range of 30° to 31°, 35° to 36°, 42.5° to 43.5°, 56.5° to 57.5°, and 62° to 63°. The negative electrode active material according to claim 1,

6. A secondary battery comprising a negative electrode, the negative electrode comprising a negative electrode active material layer and a current collector, the negative electrode active material layer comprising the negative electrode active material according to any one of claims 1 to 5.

7. An electronic device comprising the secondary battery according to claim 6.

Citation Information

Patent Citations

  • Lithium ion secondary battery electrode and lithium ion secondary battery

    JP2013054978A

  • Negative electrode active material and lithium battery employing the same material

    JP2013084601A

  • Composite active material for lithium secondary battery, manufacturing method for the same and lithium secondary battery

    JP2016149340A

  • Negative electrode active material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2019133920A

  • An anode for a lithium ion secondary battery and a secondary battery comprising the same

    KR1020220048461A